FUZZY MODELS IN PROBLEMS OF COMPLEX SYSTEMS CONTROL - Kucherenko, Ye. I.; Driuk, O. D. (Radio Electronics, Computer Science, Control, 2014)
An analytical review of existing models and methods of applied problem solving is performed. The necessity of developing of fuzzy models of mobile objects is shown. A new formal model of mobile objects control as minimization of the control error is developed. It is shown that the problem of optimal mobile objects control is to find the optimal (or suboptimal) function of mobile objects control. Depending on the values of certain external parameters, this function returns a value that determines the future direction of the mobile object movement. One of the most perspective approaches to the control function optimization is development and adjustment of fuzzy model of mobile object movement. Development of a model based on fuzzy rules will provide its flexibility. The fuzzy model as a set of production rules has been further developed. This model, unlike the existing ones, allows minimizing the error of mobile objects control. The adequacy of the developed models has been confirmed. It was shown that these models provide good mobile objects control.